Impact of Oral Health on the Quality of Life of 3 to 5-Year-Old Children: A Pilot Study - Rafaela Regina de Lima; Jader Oliva Jorge; Kelly Oliva Jorge (Archives of Current Research International, 2025)
Aims: To investigate the impact of oral health on the quality of life of children aged 3 to 5 years, of both sexes, enrolled in public and private schools in Belo Horizonte, Brazil. Study Design: Cross-sectional study. Place and Duration of Study: The study was conducted in public and private schools in Belo Horizonte, Brazil, during the year 2019. Methodology: The sample consisted of 109 children and their parents or guardians. To assess the oral health-related quality of life (OHRQoL) of preschool-aged children, the Early Childhood Oral Health Impact Scale (ECOHIS) was used. A self-administered questionnaire was also applied to collect sociodemographic data. The ECOHIS evaluates the physical, social, and psychological impacts of oral health conditions in children and their families. Results: The findings revealed a significant negative impact of oral health conditions on the OHRQoL of both the children and their families. Children from lower socioeconomic backgrounds showed a greater negative impact on family quality of life. Additionally, girls experienced a more pronounced negative effect compared to boys. Conclusion: Oral health conditions substantially affect the quality of life of children and their families, especially among those with lower socioeconomic status. These findings highlight the importance of implementing educational and preventive oral health programs targeting preschool-aged children.